Microcrédito e a democratização do mercado financeiro: o caso do banco popular em Ipatinga-MG. - Fernando Batista Pereira (2004)
This piece aims analyzing the microcredit programme of the Banco Popular de Ipatinga (Minas Gerais Brazil) focusing the possibility of the programme to supply credit service to the low-income population together with a sustainable financial structure. To do that, we have investigated the social target of the programme and its importance for the potential costumers. The dissertation is divided in four chapters, besides the introduction and the conclusion. The first chapter surveys the literature about microcredit and microfinance. The second one analyses the methodology usual by the Banco Popular and its main products supplied. Finally, on the third and fourth chapters it is discussed the main features of the clients of the programme, shedding lights on the socio-economics disparities founded on the analyses. Our final conclusion highlights that, despite the limits, the Banco Popular has been an important instrument for the democratization of the access to credit for their customers